Developing Effective Marketing Strategies for Herviolet After COVID-19 Pandemic: A Case Study of Herviolet - Soempeno, Rio Dzaki; Aprilianty, Fitri (Integrasi Sains Media, 2023)
The recent COVID-19 pandemic has limited many ethnic modern-style fashion brand’s selling and promotional activities to almost a halt. Their previous main source of income and publicity through national conventions and exhibitions, became unavailable due to pandemic policies and restrictions. These brands must now find a way to capitalize the usage of digital marketing as a way to promote and sell their product. Herviolet is one of the ethnic modern brands that were affected, and are struggling with their marketing efforts due to an ineffective marketing strategy. As stated by Herviolet’s owner, the company does not have a marketing department, goal, nor strategy. Therefore, this research is designed to create solutions towards Herviolet’s marketing strategy problems that will help them increase their brand awareness and product knowledge. An internal and external analysis will be conducted, with the latter using PESTEL and Porter’s Five Forces Analysis, and will be summarized with a SWOT Analysis. A qualitative methodology will also be conducted, using semi-structured interviews towards Herviolet’s owner and two regular customers, where the interview results will be analyzed using open coding. A monthly social media performance analysis will also be conducted, where the account insights, data, and performance will be analyzed to give an image of Herviolet’s current social media performance. From this research, 3 solutions were developed for Herviolet in order to improve their marketing strategy, brand awareness, and product knowledge.